UNDERGROUND ECONOMY DAN KEJAHATAN BIROKRAT - Darmawan, Mohammad Kemal (P2KK LIPI, 2010)
To comprehend the reality of this underground economy certainly requires an understanding of the upstream and the downstream network of the activity. Several studies about underground economy have conducted in many countries indicate that this economic activity has involved many actors. Underground economy is also a complex phenomenon, present to an important extent even in the most industrialized and developed economies. People engage in underground economic activity for a variety of reasons; among the most important are, to avoid government actions, most notably taxation and regulation. This paper is also concerned with the bureaucrats crime. It uses the context of the garment import sector in Indonesia to further analyze issues relating to corruption in both private and public sector. The author argues that blaming the bureaucrats or the private businesses alone would not do justice to the problem. Neither will it help in finding appropriate policies to solve this important problem in governance and development. Keywords: underground economy, corruption, bureaucrats crime, government, tax reform.